Future of the National Parks of India - Sankhala, Kailash (Indian Forester, 1991)
India’s National Parks are known for their beauty and rich biodiversity, some of them being recognised as World Natural Heritage Sites by UNESCO. These National Parks are under great pressure due to grazing, human population and illicit fellings. The Government Notifications relating to National Parks and legislation with a view to conservation seem to have been done without public debate and in a hurry. Their is a lack of people’s participation in the formation and conservation of National Parks. Though a large number of people are showing enthusiasm for the cause of wildlife, the system is incapable of accommodating them, thus alienating popular sentiment. Lately, the cause of Wildlife conservation has attracted interest at the highest political level. The author contends that the Wildlifee function should be separated from the Forestry function at the State-level as it has been done at the Centre. He advocates more people’s participation and better, scientific management of our natural heritage.